2022
DOI: 10.1186/s13287-022-02825-z
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells (MSCs) and their exosome in acute liver failure (ALF): a comprehensive review

Abstract: Recently, mesenchymal stromal cells (MSCs) and their derivative exosome have become a promising approach in the context of liver diseases therapy, in particular, acute liver failure (ALF). In addition to their differentiation into hepatocytes in vivo, which is partially involved in liver regeneration, MSCs support liver regeneration as a result of their appreciated competencies, such as antiapoptotic, immunomodulatory, antifibrotic, and also antioxidant attributes. Further, MSCs-secreted molecules inspire hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 213 publications
(225 reference statements)
0
23
0
Order By: Relevance
“…NAC is a precursor to GSH and can increase GSH levels to reduce covalent binding between NAPQI and proteins, eliminating ROS and preserving mitochondrial energy metabolism, thus preventing liver cell necrosis and in ammation [40,43]. Research has found that MSCs from both humans and mice can increase the survival rate of mice with APAP-induced ALF [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…NAC is a precursor to GSH and can increase GSH levels to reduce covalent binding between NAPQI and proteins, eliminating ROS and preserving mitochondrial energy metabolism, thus preventing liver cell necrosis and in ammation [40,43]. Research has found that MSCs from both humans and mice can increase the survival rate of mice with APAP-induced ALF [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Novel drug targets are being identified to combat entry of hepatotropic viruses into cells and replication such as nicotinamide in hepatitis A [ 79 ], recombinant HEV virion [ 80 ] and the newly introduced bepirovirsen in hepatitis B [ 81 ], although these are yet to be tested in acute liver failure. Emerging data from animal studies are also available on immunotherapy with agents such as thymosin alpha 1 [ 82 ], mesenchymal stem cells and their exosomes in ALF [ 83 ] as immunomodulators to prevent immune dysfunction in ALF. If successful, they would help decrease the burden on the organ pool and contribute to improving transplant free survival rates in ALF further.…”
Section: Management Of Viral Alfmentioning
confidence: 99%
“…[45][46][47] MSCs exert immunomodulatory and immunosuppressive effects in vivo and in vitro [48][49] . In several mouse models of acute liver failure, MSCs signi cantly reduce in ammatory cell in ltration, reduce apoptosis, and increase hepatocyte proliferation, thus promoting liver regeneration and improving survival [50][51][52] . MSCs have been reported to modulate adaptive immune responses, induce DC to upregulate the anti-in ammatory cytokine, IL-10, and reduce the secretion of the pro-in ammatory cytokines, TNF-α and IL-12 53 .…”
Section: Disscussionmentioning
confidence: 99%